Genotyping of a tri-allelic polymorphism by a novel melting curve assay in MTHFD1L: an association study of nonsyndromic Cleft in Ireland. - MOLLOY, ANNE (My University, 2012)
Background: Polymorphisms within the MTHFD1L gene were previously associated with risk of neural tube defects in Ireland. We sought to test the most significant MTHFD1L polymorphisms for an association with risk of cleft in an Irish cohort. This required the development of a new melting curve assay to genotype the technically challenging MTHFD1L triallelic deletion/insertion polymorphism (rs3832406). Methods: Melting curve analysis was used to genotype the MTHFD1L triallelic deletion/insertion polymorphism (rs3832406) and a Single Nucleotide Polymorphism rs17080476 in an Irish cohort consisting of 981 Irish case-parent trios and 1,008 controls. Tests for association with nonsyndromic cleft lip with or without cleft palate and cleft palate included case/control analysis, mother/control analysis and Transmission Disequilibrium Tests of case-parent trios. Results: A successful melting curve genotyping assay was developed for the deletion/insertion polymorphism (rs3832406). The TDT analysis initially showed that the rs3832406 polymorphism was associated with isolated cleft lip with or without cleft palate. However, corrected p-values indicated that this association was not significant. Conclusions: Melting Curve Analysis can be employed to successfully genotype challenging polymorphisms such as the MTHFD1L triallelic deletion/insertion polymorphism (DIP) reported here (rs3832406) and is a viable alternative to capillary electrophoresis. Corrected p-values indicate no association between MTHFD1L and risk of cleft in an Irish cohort
PUBLISHED
Keywords: MTHFD1L gene; MTHFD1L gene; Genes & Society